Amygdala–orbitofrontal connectivity predicts alcohol use two years later: a longitudinal neuroimaging study on alcohol use in adolescence. Issue 4 (23rd October 2016) - Peters, Sabine; Peper, Jiska S.; Van Duijvenvoorde, Anna C.K.; Braams, Barbara R.; Crone, Eveline A.
Abstract: This study tested the relation between cortical–subcortical functional connectivity and alcohol consumption in adolescents using an accelerated longitudinal design, as well as normative developmental patterns for these measures. Participants between ages 8 and 27 completed resting‐state neuroimaging scans at two time points separated by two years ( N  =   274 at T1, N  =   231 at T2). In addition, participants between ages 12 and 27 reported on recent and lifetime alcohol use ( N  =   193 at T1, N  =   244 at T2). Resting‐state connectivity analyses focused on amygdala–orbitofrontal connectivity given prior research linking reduced coupling between these regions to alcohol use. Mixed model analyses revealed that age had a cubic relationship with alcohol use, with little to no use in childhood, steep increases in adolescence and leveling off in adulthood. No age effects were found for amygdala–OFC connectivity. Prediction analyses showed that left amygdala–orbitofrontal connectivity at the first time point predicted recent and lifetime alcohol use two years later. There was no evidence for the reversed relation, suggesting that brain connectivity measures precede explorative risk‐taking behavior in adolescence, possibly because decreased subcortical–frontal connectivity biases towards more explorative or risky behavior. Abstract : Amygdala‐orbitofrontal connectivity predicted alcohol use two years later, but not vice versa, suggesting that brain connectivity precedes explorative risk‐taking behavior in adolescence.